2023
DOI: 10.32958/gastoria.1205831
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Indication and Gastronomy Tourism in the Case of Kayseri̇ Bünyan and Akkişla Gi̇laburusu (Guelder-Rose)

Abstract: Within the context of gastronomic tourism, the interest of the tourists is very high for the local food and beverages specific to a region. Therefore, it is necessary to perform studies to enable the sustainability of gastronomic tourism while preserving the regional cuisine culture to hand down the next generations. Subjects of these studies also have great importance to increase the recognition of local products by taking them under protection through the geographical indication application. In Kayseri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Traditionally, VO has proactively mitigated certain gastrointestinal and renal disorders. Additionally, it has been harnessed for therapeutic interventions encompassing ailments like cough, cold, elevated blood pressure, diabetes, ulcerations, hepatic afflictions, rheumatic discomfort, and tuberculosis (Al et al, 2017;Altun et al, 2009;Eryılmaz et al, 2013;Kızılay et al, 2019;Sabur & Güneş, 2023;Česonienė et al, 2014). It has been reported that the phenolic acid, ascorbic acid, and organic acid contained in the fruit of VO can reduce urinary pH and prevent the formation of kidney stones and that VO phenolics can modulate cellular membrane dynamics (Kajszczak et al, 2020;Małgorzata et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, VO has proactively mitigated certain gastrointestinal and renal disorders. Additionally, it has been harnessed for therapeutic interventions encompassing ailments like cough, cold, elevated blood pressure, diabetes, ulcerations, hepatic afflictions, rheumatic discomfort, and tuberculosis (Al et al, 2017;Altun et al, 2009;Eryılmaz et al, 2013;Kızılay et al, 2019;Sabur & Güneş, 2023;Česonienė et al, 2014). It has been reported that the phenolic acid, ascorbic acid, and organic acid contained in the fruit of VO can reduce urinary pH and prevent the formation of kidney stones and that VO phenolics can modulate cellular membrane dynamics (Kajszczak et al, 2020;Małgorzata et al, 2019).…”
Section: Introductionmentioning
confidence: 99%